Short-term growth, movement and response of European eel Anguilla anguilla to re-meandering of a small English chalk stream - Champkin James D.; Bašić Tea; Haubrock Phillip J.; Balzani Paride; Sayer Carl D.; George Laura K.; Godard Michael J.; Vilizzi Lorenzo; Copp Gordon H. (Knowledge and Management of Aquatic Ecosystems)
In recent decades, the population of European eel Anguilla anguilla has strongly declined and the stock is outside safe biological limits. Freshwater habitat degradation has been cited as a key causal factor in the European eel decline, but there are limited studies assessing the responses of this species to river habitat restoration efforts. This study utilized mark-and-recapture data from annual electrofishing surveys conducted between 2009 and 2014 to describe European eel population density and size structure (length, weight) in the River Glaven − a chalk stream in eastern England. Short-term effects of river restoration on European eel were assessed via a Before-After-Control-Impact experimental design. Of the recaptured individuals, 73% were sedentary and the rest mobile. Despite re-meandering work increasing habitat heterogeneity in the restoration reach relative to the control reach, no change in European eel density or size structure was detected across treatments and time. While length and weight increased in the downstream control reach over the study period, density declined. This can be attributed to various local stressors such as barriers to European eel migration, as well as broader range-scale causes including climatic and oceanic factors. Although further research is ideally necessary to ensure adequate sample sizes, as well as to provide long-term monitoring of eel responses to river restoration, this study emphasizes the need for whole-catchment efforts in European eel conservation that combine river–floodplain restoration with greatly improved fish passage.